CRIMINISTRATIVE LAW: DEVELOPMENTS AND CHALLENGES IN INDONESIA - Naibaho, Nathalina; Harkrisnowo, Harkristuti; AR, Suhariyono; Wibisana, Andri Gunawan (Indonesia Law Review, 2021)
The borderlines between core criminal law and administrative law developed in such a way that it became increasingly difficult to draw a clear and a firm category while dividing line between those. The category of a measure as administrative or criminal is far from being theoretical as it preconditions the applicable legal regime and especially the level of procedural safeguards benefiting to those sanctioned. This paper is questioning the gray area belonging to something in between criminal and administrative law and discussing the rule and the role of criminal law and administrative law in action when the later comprehend punitive administrative sanctions. Several circumstances need to be considered in order to determine the appropriate sanction to fill the gap. This article also suggests the use of “una via principle” as an approach to unpack the gray area in the role of criminal and administrative law, specifically in tax law case.